Transnational Generations in the Arab Gulf States and Beyond - Matsukawa, Kyoko; Watanabe, Akiko; Babar, Zahra R. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book examines the recent migration phenomenon in the Arab Gulf states for work and residence. It sheds light on the transnationality of diverse groups of migrants from different generations, and unpacks how migrants' multiple senses of belonging, orientations and adaptive strategies have shaped contemporary migration in the Gulf region. In turn, the analysis presented here shows how the Arab Gulf states' citizenship and educational policies affect second-generation migrants in particular. Through a series of fine-grained ethnographic case studies, the authors demonstrate the ways in which these second-generation migrants construct their identities in relation to their putative 'home' country in the Gulf as well as their complex relationship to their parents' countries of origin. This is what underpins the deeply transnational character of their lives, choices and notions of belonging. While migration scholars often situate these groups as 'temporary', this does not in fact capture the reality of temporariness for the migrants themselves, their children or their dependants. The result is a complex and ongoing construction of identity that shapes the way of life for millions of migrants. Relevant to scholars of migration and international studies, particularly focused on the Middle East, Transnational Generations in the Arab Gulf States and Beyond is also of interest to social scientists researching student mobility in higher education, intergenerational families, identity politics and globalisation.
1. Introduction -- 2. Long-term Residency Rights, Citizenship Schemes and the Attraction of Talents: Transnational Presence over Generations in the Face of Investment Migration -- 3. Integration in Host Societies beyond the Dependence Visa: Migrant Children in Gulf Cooperation Council Countries -- 4. The Impediments for Second-generation Migrants to Enter Higher Education in Gulf Cooperation Council Countries -- 5. Motives for Choosing to Study at International Branch Campuses in Qatar: Possibilities and Challenges for Qatari and Foreign Students -- 6. Children of Skilled Overseas Filipino Workers in the United Arab Emirates and Their Versions of Citizenship -- 7. The Return Experience and the Perpetual In-betweenness of Gulf-born Non-resident Indians: Analysis of Cases in Kuwait -- 8. Belonging as Familiarity: The Bitterness of Permanent Temporariness among Qatar-born Egyptians -- 9. Privileged but Immobile: Citizenship and Career Paths for the Youth of Bicultural Kuwaiti-Filipino Families -- 10. Expressing Identity through the Dressed Body: A Study of Iranian Migrants in Gulf Cooperation Council Countries.
Keywords: Emigration and immigration; Asia -- Politics and government; Anthropology; Political science; Identity politics; Education, Higher; Human Migration; Asian Politics; Anthropology; Politics and International Studies; Identity Politics; Higher Education